Kesiapan Digital dalam Layanan Kesehatan: Kajian Technology Acceptance Model (TAM) pada Rekam Medis Elektronik Rumah Sakit - Hurit, Theofila Barek; Kurniawan, Afif; Tjoro, Silvia Haniwijaya (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
The development of information technology has encouraged the implementation of Electronic Medical Records (EMR) to modernize and improve the efficiency, effectiveness, and quality of outpatient services in hospitals. This study aims to analyze the influence of external variables, perceived usefulness, perceived ease of use, attitude towards using, and behavioral intention to use on the actual Electronic Medical Record system at PKU Muhammadiyah Hospital in Surabaya. This study is an analytical observational study with a quantitative approach involving 29 employees as respondents using a questionnaire as a data collection instrument, which was then analyzed using multiple linear regression. Regression tests show that the variables Attitude Towards Using (0.000) and Behavioral Intention To Use (0.000) have a significant effect on the actual use of the system. This means that users' positive attitudes towards the electronic medical record system play a major role in encouraging the adoption and actual use of the system. This implies that the better the users' attitude toward the system, the higher the likelihood that they will consistently use the system in the hospital environment. Psychological factors and users' internal motivation are more decisive in the success of technology adoption than other factors such as experience or direct assessment of benefits.